(3SaQ GdSYGOI hSajQ GdEaGOIs - (3Ydj Hf eMeO Hf YHO GdUeO GdgeOGfj GdeUQj GdSNGhj GdTGaYj, CHh GdMSf, Yde GdOjf,J (B643 (3g` s ((3eMeO Hf YHO GdefYe Hf Ydi GdbQTi s)
(3ChdgG (B:s
(3HGSe Gddg GdPi HGSeg JJaJM GdChGFd CeG HYO gPG cJGH SaQ GdSYGOI hSajQ GdEaGOI jMJad HGdeYGfi GdYLjHI s
(3BNQgG (B:s
(3JSei GdYQH GdbGajI GdeYjHI GdaGSOI (B: (3GdJMQjO hPdc eCNhP ef GdMQO ai GdQLdjf hGddg CYde s
(3GdfSNI HgG MhGTs
(3YdjgG Jedc SfI (B884s
(3fSNI KGfjI s
(3hQO aj agQS GdeYgO (B( 1 / 357 ) (3Cfg (B: " (3cJGH aj GddZI TQM ajg eYGfj GdCeKdI GdhGQOI aj GdeaUd aj UfGYI GdEYQGH ddReNTQj TQkMG dZhjG (B" (3HjfeG de ojUQM HPdc eDdag aj GdebOeIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3GdfMhs